Potential of Tinospora crispa as a Hypocholesterolemic agent in rabbits - Amom, Zulkhairi; Bahari, Hasnah; Md Shah, Zamree; Mohd Arshad, Mohd Shahidan; Ibrahim, Nursakinah; Othman, Fauziah; Ismail, Maznah; Baharuldin, Mohamad Taufik Hidayat; Mohd Moklas, Mohamad Aris; Abdul Kadir, Khairul Kamilah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2009)
Introduction: Hypercholesterolemia is the major cause of cardiovascular disturbances. The influence of Tinospora crispa on atherosclerotic plaque formation in rabbits fed with high cholesterol diet was investigated. Methods: Thirty male New Zealand White rabbits were divided into 6 groups. The negative control (NC) and positive control (PC) groups were used as a negative and positive (0.5% cholesterol) control. The simvastatin control (SC) group was given a high cholesterol diet (HCD) with 5mg/kg simvastatin. Treatment groups T150 and T450 were given HCD with supplementation of 150,300 and 450mg/kg of T.crispa extract respectively for 10 weeks. Blood was collected from ear vein for plasma analysis while the aortas were excised and examined microscopically. Results: Comparison within groups showed that PC, T300 and T450 had a significant increase (p<0.05) in total cholesterol level throughout the study. The groups supplemented with T.crispa (T150, T300 and T450) were significantly higher (p<0.05) in high density lipoprotein (HDL) level by 10.7-fold, significantly higher (p<0.05) in total antioxidant activity and had a significantly lower (p<0.05) LDL level compared to PC at week 10. At week 10, T450 had significantly highest (p<0.05) glutathione peroxidase and superoxide dismutase levels compared to PC. No foam cell formation was visible in the aorta of rabbits,in groups NC,SC and T450. However , there was visible foam cell formation in the aorta of groups PC, T150 and T300. Conclusion: This study suggest that supplementation of 450mg/kg of T.crispa extract would be able to reduce or retard the progression of atherosclerotic plaque development induced by dietary cholesterol.